Pharmacological modulation of HDAC1 and HDAC6 in vivo in a zebrafish model: Therapeutic implications for Parkinson's disease - Brígida R Pinho (2016)
Histone deacetylases (HDACs) are key epigenetic enzymes and emerging drug targets in cancer and neurodegeneration. Pan-HDAC inhibitors provided neuroprotection in Parkinson's Disease (PD) models, however, the HDAC isoforms with highest neuroprotective potential remain unknown. Zebrafish larvae (powerful pharmacological testing tools bridging cellular and in vivo studies) have thus far been used in PD modelling with limited phenotypic characterization. Here we characterize the behavioural and metabolic phenotypes of a zebrafish PD model induced with MPP+, assess the feasibility of targeting zebrafish HDAC1 and HDAC6 isoforms, and test the in vivo effects of their selective inhibitors MS-275 and tubastatin A, respectively. MPP+ induced a concentration-dependent decrease in metabolic activity and sensorimotor reflexes, and induced locomotor impairments rescuable by the dopaminergic agonist apomorphine. Zebrafish HDAC1 and HDAC6 isoforms show high sequence identity with mammalian homologues at the deacetylase active sites, and pharmacological inhibition increased acetylation of their respective histone and tubulin targets. MS-275 and tubastatin rescued the MPP+-induced decrease in diencephalic tyrosine hydroxylase immunofluorescence and in whole-larvae metabolic activity, without modifying mitochondria) complex activity or biogenesis. MS-275 or tubastatin alone modulated spontaneous locomotion. When combined with MPP+, however, neither MS-275 nor tubastatin rescued locomotor impairments, although tubastatin did ameliorate the head-reflex impairment. This study demonstrates the feasibility of pharmacologically targeting the zebrafish HDAC1 and HDAC6 isoforms, and indicates that their inhibition can rescue cellular metabolism in a PD model. Absence of improvement in locomotion, however, suggests that monotherapy with either HDAC1 or HDAC6 inhibitors is unlikely to provide strong benefits in PD. This study highlights parameters dependent on the integrity of zebrafish neuronal circuits as a valuable complement to cell-based studies. Also, the demonstrated feasibility of pharmacologically targeting HDAC1 and HDAC6 in this organism paves the way for future studies investigating HDAC inhibitors in other diseases modelled in zebrafish.